Toward a better understanding of the environmental impacts of expanding farmer-led irrigation in Sub-Saharan Africa: An exploratory assessment of irrigation-induced risk of nutrient water pollution in Ethiopia - Xie, Hua; Dile, Yihun T.; Ringler, Claudia; Srinivasa, R.; Worqlul, Abeyou Wale (IOP Publishing, 2023)
Irrigation, and especially farmer-led irrigation, is considered to be a promising option for enhancing agricultural productivity in Sub-Saharan Africa. However, there is a lack of thorough understanding of the impacts of irrigation development on environment. Past discussions are mainly limited to the water depletion and hydrological regime change effect of irrigation. This paper presents a study to narrow the knowledge gap by assessing nutrient water pollution risk induced by the expansion of farmer-led irrigation in Ethiopia. Using household survey data collected from four woredas in Ethiopia where irrigated crop production currently concentrates, we first evaluate the impact of irrigation on cropping intensity and annual consumption level of fertilizers and then use the findings of the household survey data analysis to support conceptualization of a modeling framework for assessing agricultural nutrient water pollution risk from farmer-led irrigation development in Ethiopia at national scale. We project that overall farmer-led irrigation development in Ethiopia will lead to a gentle increase in national total of agricultural nutrient loadings. This result helps justify the endeavor of promoting farmer-led irrigation in Ethiopia. On the other hand, the projected nutrient flow and nutrient loading growth rate related to the farmer-led irrigation expansion are highly heterogeneous spatially, and risk of local water quality deterioration exists. There is still need to make investment to ensure the environmental sustainability of farmer-led irrigation development.